Ecological status of the sediment communities of Castries harbour, St Lucia, West Indies - Shim, David (Elsevier LondonGB, 1987)
Examines the microfauna of the sediments of Castries Harbour, using community factors and diversity indices. Shows that although the outer harbour supports a healthy community, the inner section shows signs of environmental stress resulting from a variety of anthropogenic influences in that part of the harbour. In comparison with some other harbours in the region, however, Castries Harbour appears to support a more healthy and diverse marine community, indicating a substantially lower level of environmental stress.